2017 IEEE International Conference on Image Processing (ICIP) 2017
DOI: 10.1109/icip.2017.8296611
|View full text |Cite
|
Sign up to set email alerts
|

Deep class-aware image denoising

Abstract: The increasing demand for high image quality in mobile devices brings forth the need for better computational enhancement techniques, and image denoising in particular. At the same time, the images captured by these devices can be categorized into a small set of semantic classes. However simple, this observation has not been exploited in image denoising until now. In this paper, we demonstrate how the reconstruction quality improves when a denoiser is aware of the type of content in the image. To this end, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 60 publications
0
47
0
1
Order By: Relevance
“…Zhang et al [26] constructed a 20-layer feed-forward denoising convolutional neural networks with residual learning for Gaussian denoising. Remez et al trained 20-layer CNNs for each object category respectively and showed good performance for either Gaussian denoising [15] or Poisson denoising [16]. Zhang et al [27] proposed FFDNet adopting orthogonal regularization to enhance the generalization ability of Gaussian denoising.…”
Section: Image Denoisingmentioning
confidence: 99%
“…Zhang et al [26] constructed a 20-layer feed-forward denoising convolutional neural networks with residual learning for Gaussian denoising. Remez et al trained 20-layer CNNs for each object category respectively and showed good performance for either Gaussian denoising [15] or Poisson denoising [16]. Zhang et al [27] proposed FFDNet adopting orthogonal regularization to enhance the generalization ability of Gaussian denoising.…”
Section: Image Denoisingmentioning
confidence: 99%
“…Machine learning-based techniques are widely discussed, studied and applied for image classification, image recognition, and object detection in many fields [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The related application cases of machine learning-based image detection and classification are introduced as follows.…”
Section: Related Workmentioning
confidence: 99%
“…For the other applications [15][16][17][18][19][20][21], Zhang et al [15] proposed a covariance descriptor that combined visual and geometric information. Moreover, this work integrated a classification framework with dictionary learning for the object recognition of 3D point clouds.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Batch normalization [20] improves the internal covariate shift by incorporating a normalization step and a scale and shift step before the nonlinearity in each layer. The merits are fast training, better performance, and low sensitivity to initialization.…”
Section: B Batch Normalizationmentioning
confidence: 99%